Grape juice concentrate alleviates epididymis and sperm damage in cadmium‐intoxicated rats. Issue 2 (5th June 2017) - Lamas, Celina de A.; Cuquetto‐Leite, Livia; do Nascimento da Silva, Emanueli; Thomazini, Bruna F.; Cordeiro, Gabriel da S.; Predes, Fabrícia de S.; Gollücke, Andrea P.B.; Dolder, Heidi
Summary: The possibility of long‐term grape juice concentrate (GJC) consumption conferring a protective effect against cadmium (Cd)‐induced damage to the epididymis, completely preserving sperm profile, was evaluated here for the first time in the scientific literature. Male Wistar rats ( n = 6/per group) received an intraperitoneal Cd injection (1.2 mg/Kg) at age 80 days and GJC (2 g/Kg) by gavage from 50 days until 136 days old. Groups receiving either Cd or GJC were added. An intraperitoneal injection of saline (0.9%) and water by gavage was administered in the absence of treatment with Cd or GJC. Animals were anaesthetized and exsanguinated at 136 days; the vas deferens, left testis and epididymis were removed; and perfusion continued with fixative. The right epididymis was collected for morphological analysis. Cd had a devastating effect demonstrated by reduced sperm count in testes and epididymis, sperm production and normal sperm count, besides increased epididymis sperm transit time and completely disorganized morphology. These alterations were attributed to higher Cd levels in the testes and a lipid peroxidation (LP) process. Consumption of GJC plus Cd intoxication was effective, reducing metal accumulation and LP. Consequently, we could identify a preserved sperm profile, with improvement in testis and epididymis sperm count, normal sperm structure and sperm transit time. Moreover, GJC extends its protective effect to the epididymis, allowing complete re‐establishment of its morphology, ensuring successful sperm maturation process. In conclusion, our study indicates long‐term GJC as a promising therapy against reproductive chemical intoxication injury damage, preserving sperm prior to ejaculation.